2012
DOI: 10.1673/031.012.15301
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Biology and Functional Response ofDineulophus phtorimaeae, a Natural Enemy of the Tomato Moth,Tuta absoluta

Abstract: The tomato moth, Tuta absoluta (Lepidoptera: Gelechiidae), is a major pest in South America and is at present an important invasive species in the Mediterranean Basin. The larval stadium mines leaves, stems, and fruits, and chemical control is the most used control method in both its original range and the invaded distribution regions. Since current T. absoluta control strategies seem limited, biological control is a prominent tool to be applied abroad. The naturally occurring larval ectoparasitoid in Argentin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 36 publications
1
9
1
1
Order By: Relevance
“…Thus, perhaps it depends on the parasitoid egg development strategy (proovigeny versus synovigeny), which is similar to the observation of Savino et al (2012) who demonstrated mature egg lengths in Dineulophus phtorimaeae (extremely synovigenic) that were equal in size over the range of the adult female lifetime. In contrast to our study, Ghara and Borges (2010) had shown that the Apocryptophagus agraensis (proovigenic parasitoid) produces fewer but larger eggs over her lifetime.…”
Section: Suggested Thatsupporting
confidence: 74%
“…Thus, perhaps it depends on the parasitoid egg development strategy (proovigeny versus synovigeny), which is similar to the observation of Savino et al (2012) who demonstrated mature egg lengths in Dineulophus phtorimaeae (extremely synovigenic) that were equal in size over the range of the adult female lifetime. In contrast to our study, Ghara and Borges (2010) had shown that the Apocryptophagus agraensis (proovigenic parasitoid) produces fewer but larger eggs over her lifetime.…”
Section: Suggested Thatsupporting
confidence: 74%
“…The moth originates from South America and was spread to Europe, North Africa, Asia and recently in the Middle East over the past ten years (Desneux, 2011;FAO, 2016;Alberto Urbaneja, 2012). Their larvae damage leaves, fruits, and stems (Savino et al, 2012), causing considerable losses on tomato yield. Losses of 50-100% have been reported on tomato (EPPO, 2005;Gebrelebanos, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the ectoparasitoid Dineulophus phthorimaeae de Santis (Hymenoptera: Eulophidae) shows density-independent proportions of parasitized and host-fed larvae (type I FR) (Savino et al, 2012).…”
Section: Discussionmentioning
confidence: 99%